Food Waste Behaviour and Awareness of Malaysian - Chooi Lin Phooi; Elisa Azura Azman; Roslan Ismail; Jasmin Arif Shah; Evelyn Shin Rou Koay (Scientifica)
Food waste is a vast issue global, including in Malaysia. Food waste brings negative impacts, including increasing food production costs, impact on human health, and environmental degradation. Malaysian’s animal- and plant-based diet preferences affected the desired food waste decomposition method as most of the methods only allow plant-based material to be utilized as food waste compost. The objectives of this study were to understand Malaysians' awareness of food waste behaviour and the food waste component for the decomposition. Malaysians usually produce more plant-based food waste than animal-based food waste. Most Malaysians have a high awareness of causes and impact of food waste, but they lack action on food waste reduction. Bio-compost is believed to be the most effective method to manage food waste, and most of them were willing to have it at home. However, some of them are unwilling to have a compost pile at home because there is no time to take care of it.